From East to West – the Image of Saint George in the Art of the Middle Ages - Cristina Safta (Anastasis: Research in Medieval Culture and Art)
Among the representative figures of the Middle Ages, symbolizing courage, verticality, spirit of sacrifice, the Saint and Great Martyr George stands out by far. Considered a hero and a protector, the saint was an example to all those who showed their virtue and bravery in the fight to defend faith. Impressive is the large number of countries that settled under his rule, starting with the Kingdom of England, Portugal, Spain; almost the whole of Europe invoked protection through the flags and blazons dedicated to the Holy Victor. In this context, it was natural for a large number of religious edifices to be dedicated to Saint George, and his representations in sculpture, painting, embroidery, were extremely valuable not only from a religious point of view in invoking divine help, but also from an artistic one.